VEHICLE ROUTING OF PARCEL POST DISTRIBUTION IN NONTHABURI USING PARTICLE SWARM OPTIMIZATION - Deesoon, Nilnate; Suwannarongsri , Supaporn (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The research applied the Particle Swarm Optimization along with Local Search including Swap and 2-opt to plan the route arrangement of parcel post distribution of Thailand Post in Nonthaburi. The research tested appropriate parameters for the proposed algorithm including acceleration factor for local best position equal to 2, acceleration factors for global best position equal to 4 and inertia weight equal to 0.9. The results showed that the proposed algorithm could calculate shortest route is equal to 76.1 kilometers using 2.20 seconds. In addition, the research also tested the performance of algorithm which was proposed with 10 benchmark problems which was travelling salesman problem and compared the solutions including the research problem, ulysses16 and ulysses22 with the Nearest Neighbor Algorithm. It appeared that the algorithm which was proposed could search solutions all benchmark problems. The eil51 problem had the highest error deviation equal to 2.34 percent and could search all solutions better than Nearest Neighbor Algorithm